Aktivitas Belajar Menggunakan Model Kooperatif Tipe Make A Match di Sekolah Dasar - Dinni Ramayani; Elfia Sukma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims to describe an increase in students' learning activities using cooperative models of make a match type in Class IV SDN 09 Bandar Buat.This type of research is PTK with qualitative and quantitative approaches. The experiment was conducted in two cycles. The research data in the form of observations.The research subjects were teachers and students of class IV.RPP research results 90.62% the first cycle, the second cycle 100% (SB).Implementation of aspects of teacher learning cycle I 81.25% (B), the second cycle to 96.87% (SB). Aspects of the first cycle students 76.56% (C), 96.87% second cycle (SB). Cycle I student learning activities visual activities67.68% (C), writing activities 65.52% (K), oral activities 58.19%, (C), motor activities 81.03% (B). Cycle II visual activities 87.06% (B), writing activities 81.89% (B), oral activities 72.41% (C), motor activities 93.96% (SB). It can be concluded in the study that the cooperative model types make a match can improve students' learning activities.Keywords : Make A Match, Thematic Integrated, Learning Activities